صلاة الجمعة والسيد عثمان بن عبد الله العلوي في مخطوطة كتابه "الأجوبة على مسائل الجمعة" - Naufal Ramadhan; Titi Farhanah; Muhammad Anas (LITTERATURA: Jurnal Bahasa dan Sastra, 2023)
This study discusses the manuscript "al-Ajwibah 'alá Masā'il al-Jum'ah" by Sayyid Usman bin Abdullah al-Alawi, known as Mufti Betawi, which is kept at Leiden University in the Netherlands. This study aims to reveal the opinion of the playwright and his views on the issue of the Friday prayers in Pekojan, which occurred in 1896 AD, by using historical methods to uncover the causes of this event. The results of the study show the answers of Sayyid Othman and his fatwa to questions raised by the Betawi people regarding Friday prayers and provisions related to them, including whether Friday prayers are allowed in one area, the law of repeating midday prayers, the validity requirements related to the place where prayers are held, the law on prayers being led by someone other than a preacher, and the law on appointing a prayer priest. This manuscript ends with hadiths relating to the primacy of worship on Friday and reminders taken from the book "Ihya Ulumuddin" by Imam Al-Ghazali. This study contributes to the author's statement regarding the issue of Friday prayers in the past, which is associated with the context of the Betawi community in Pekojan. The research results are expected to provide insight into this region's history and religious traditions.